Предмет: Математика,
автор: Ranis1808
Решите уравнение (2х – 1)*(2х + 3)*(3х – 2)*(3х +4)=35
Ответы
Автор ответа:
0
(2х-1)*(2х+3)*(3х-2)*(3х+4)=35
Сначала упрощаем уравнение:
1х*5х*1х*7х=35
Теперь начинаем умножать
1х*5х=5х
5х*1х=5х
5х*7х=х(5*7)
35х=35
х=35:35
х=1
Сначала упрощаем уравнение:
1х*5х*1х*7х=35
Теперь начинаем умножать
1х*5х=5х
5х*1х=5х
5х*7х=х(5*7)
35х=35
х=35:35
х=1
Автор ответа:
0
спасибо
Похожие вопросы
Предмет: Геометрия,
автор: Аноним
Предмет: Геометрия,
автор: ilmirazajnitova
Предмет: Литература,
автор: Alisa97538
Предмет: Математика,
автор: lumpova79
Предмет: История,
автор: 8923461